Integrating multi-national teams: over a decade of lessons learned in Chiapas with Partners in Health-Mexico - Palazuelos, Daniel; Flores, Hugo; Macias, Valeria (Frontiers in Public Health, 2024)
In a globalized world where pathology and risk can flow freely across borders, the discipline of global health equity has proposed to meet this challenge with an equal exchange of solutions, and people working toward those solutions. Considering the history of colonialism, ongoing economic exploitation, and gaping inequities across and within countries, these efforts must be taken with care. The Partners In Health program in Chiapas, Mexico was founded in 2011 by a team of leaders from both the United States and Mexico to strengthen the public health and care delivery systems serving impoverished rural populations. Key to the strategy has been to marshal funding, knowledge, and expertise from elite institutions in both the United States and Mexico for the benefit of an area that previously had rarely seen such inputs, but always in close partnership with local leaders and community processes. With now over a decade of experience, several key lessons have emerged in both what was done well and what continues to present ongoing challenges. Top successes include: effective recruitment and retention strategies for attracting talented Mexican clinicians to perform their social service year in previously unappealing rural placements; using effective fund-raising strategies from multinational sources to ensure the health care delivered can be exemplary; and effectively integrating volunteer clinicians from high-income contexts in a way that benefits the local staff, the foreign visitors, and their home institutions. A few chief ongoing challenges remain: how to work with local communities to receive foreign visitors; how to hire, develop, and appropriately pay a diverse workforce that comes with differing expectations for their professional development; and how to embed research in non-extractive ways. Our community case study suggests that multinational global health teams can be successful if they share the goal of achieving mutual benefit through an equity lens, and are able to apply creativity and humility to form deep partnerships.